A Longitudinal Examination of Racial Identity and Racial Discrimination Among African American Adolescents - Seaton, Eleanor K. (2009)
This study tested the longitudinal association between perceptions of racial discrimination and racial identity among a sample of 219 African American adolescents, aged 14 to 18. Structural equation modeling was used to test relations between perceptions of racial discrimination and racial identity dimensions, namely racial centrality, private regard, and public regard at three time points. The results indicated that perceived racial discrimination at Time 1 was negatively linked to public regard at Time 2. Nested analyses using age were conducted and perceptions of racial discrimination at Time 2 were negatively linked to private regard at Time 3 among older adolescents. The findings imply that perceived racial discrimination is linked to negative views that the broader society has of African Americans.